Suitability of Sm3+-Substituted SrTiO3 as anode materials for solid oxide fuel cells: A correlation between structural and electrical properties - Singh S.; Pandey R.; Presto S.; Carpanese M.P.; Barbucci A.; Viviani M.; Singh P. (My University, 2025)
Perovskite anodes, nowadays, are used in any solid oxide fuel cell (SOFC) instead of conventional nickel/yttria-stabilized zirconia (Ni/YSZ) anodes due to their better redox and electrochemical stability. A few compositions of samarium-substituted strontium titanate perovskite, SmxSr1-xTiO3-δ (x = 0.00, 0.05, 0.10, 0.15, and 0.20), were synthesized via the citrate-nitrate auto-combustion route. The XRD patterns of these compositions confirm that the solid solubility limit of Sm in SrTiO3 is x < 0.15. The X-ray Rietveld refinement for all samples indicated the perovskite cubic structure with a Pm3mspace group at room temperature. The EDX mapping of the field emission scanning electron microscope (FESEM) micrographs of all compositions depicted a lower oxygen content in the specimens respect to the nominal value. This lower oxygen content in the samples were also confirmed via XPS study. The grain sizes of SmxSr1-xTiO3 samples were found to increase up to x = 0.10 and it decreases for the composition with x > 0.10. The AC conductivity spectra were fitted by Jonscher's power law in the temperature range of 500-700 °C and scaled with the help of the Ghosh and Summerfield scaling model taking vH and σdc T as the scaling parameters. The scaling behaviour of the samples showed that the conduction mechanism depends on temperature at higher frequencies. Further, a study of the conduction mechanism unveiled that small polaron hopping occurred with the formation of electrons. The electrical conductivity, in the H2 atmosphere, of the Sm0.10Sr0.90TiO3 sample was found to be 2.7 × 10-1 S cm-1 at 650 °C, which is the highest among the other compositions. Hence, the composition Sm0.10Sr0.90TiO3 can be considered as a promising material for the application as the anode in SOFCs. © 2019 by the authors.